Phylogeography of the giant honey bees based on mitochondrial gene sequences - Bhatta, Chet P.; Zajonz, Sarah C.; Smith, Deborah R. (Frontiers in Bee Science, 2024)
We carried out a phylogenetic analysis of the giant honey bees using mitochondrial cox1 and cox2 gene sequences analysed with maximum likelihood methods. Our goal was to resolve phylogenetic relationships among Apis laboriosa, and the Apis dorsata subspecies A. d. dorsata, A. d. binghami, and A. d. breviligula, the last two of which have been proposed as full species by several authors. We obtained strong support for four clades within A. dorsata in the broad sense: the three subspecies or species mentioned above, and a fourth lineage from south India. However, our analysis did not resolve the phylogenetic relationships among the four lineages within A. dorsata in the broad sense. Recognition of these distinct lineages is important for conservation planning, so that their individual distributions, ecologies, and migration patterns can be taken into account.